Reviving audience studies. Issue 1 (1st January 2017) - Gray, Jonathan
ABSTRACT: Audience measurement data are increasingly central to what many media corporations produce, yet much of these data are inaccessible to scholars. I therefore argue that cultural studies is in need of an audience studies revival. Fan studies continues at strength, but a wider range of audience studies is required to counter and to interrogate the occasional proclamations that companies such as Netflix, Facebook, and Google share with us about audiences and users.